Formal estimation of the random component in global maps of total electron content - Choliy, V.Ya. (Advances in Astronomy and Space Physics, 2016)
Random component of the total electron content (TEC) maps, produced by global navigation satellite system processing centres, was analysed. Helmert transform (HT) and two-dimension singular spectrum analysis (2dSSA) were used. Optimal parameters (in the sense calculation speed versus quality) of the 2dSSA windows were determined along with precision estimations.